Application of technology of utilization associated petroleum gas for power generation - Vysotskiy, Andrey V. (Видавництво Львівської політехніки, 2013)
There are power plants, whose application would be most practical for primary crude oil processing stations. The power plant is intended for generating electricity as well as, if necessary, for using of heating energy. As well as the other power plants under control of the operator’s console, the reception department operates an industrial programmable controller. The controller manages the operation of the discrete and analog input/output to which measuring instruments are connected (flow meters, level meters, temperature sensors, etc.). The number of measuring instruments and actuators, if necessary, is determined by the process diagram of power plant for the oil processing unit. Hence, most active oil and refinery іnterprises are looking for the application of intelligent and integrated in production manufacturing systems of cogeneration in order to meet the customer demands and be the winners in the competitive market in that field. With available technologies and systems in the field of cogeneration and its related technologies, such application for primary crude oil processing is a reality and can meet the need of the enterprises. Today technical mangers are confused with varying equipment that prevail in this field. This article is aimed at overcoming the confusion with the new technologies that have been generated in the past five years. Further, this paper showes that all these new proposals are indeed very important and can be applicable for primary crude oil processing and cogeneration. Finally, this article focuses on latest research developments towards modern cogeneration system for primary crude oil processing stations.
Keywords: cogeneration; distributed control system; associated petroleum gas; monitoring and archiving of the data; control system